ANALISIS MANAJEMEN KONTEN BAHASA ARAB PADA AKUN INSTAGRAM BERDASARKAN TEORI THE CIRCULAR MODEL OF SOME - Hamzah, Muhammad Abi; Mufidah, Nuril; Muhammad, Nawawi Aulia; Boy, La (Jurnal Manajemen Pendidikan, 2025)
Social media has become an important tool for disseminating Arabic educational content, but effective content management strategies on platforms such as Instagram have rarely been studied in depth. This study aims to analyze Arabic content management on the Instagram account @santri_pedia.id using Regina Luttrell's The Circular Model of Social Media Engagement (SOME), which includes the stages of Share, Optimize, Manage, and Engage. This study employs a qualitative approach with a case study design. The research subject is the @santri_pedia.id account and its management team. Data was collected through in-depth interviews, direct observation of account activities, and content documentation. Data analysis was conducted using the Miles and Huberman model, through the stages of data reduction, data presentation, and conclusion drawing, focusing on the four main aspects of the SOME model. The results of the study indicate that @santri_pedia.id has implemented most of the SOME principles, particularly in the Share aspect through the adaptation of course materials and Engage through active interactions such as quizzes and polls. Optimization is carried out through insight analysis and community collaboration, but the use of hashtags and content scheduling still needs improvement. Content management is done manually without a structured editorial system, although the division of team roles is clear.